Brazilian climate politics 2005–2012: ambivalence and paradox. (22nd May 2014) - Viola, Eduardo; Franchini, Matías
<x xml:space="preserve">Abstract</x> Climate change has become a powerful social and political driver of our time. Within this context, progressive national and international societies are faced with a central challenge: how can reformist forces become strong enough to bypass the efforts of conservative forces and initiate a rapid and profound response to the climate crisis? This article reviews the politics of climate change in Brazil between 2005 and 2012 with reference to this central societal challenge, focusing on reformist and conservative actors such as economic and social forces, as well as the role of the government. This review identifies three periods: first, 2005–2008, when reformist forces grew strongly from a weak base; second, 2009–2010, when there was a peak in influence of reformist forces, while at the same time as conservative forces were growing strong; and third, 2011–2012, when conservative forces became predominant and were strongly supported by the government. WIREs Clim Change 2014, 5:677–688. doi: 10.1002/wcc.289 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.